Effectiveness of Problem-Based Learning Model on Students' Learning Outcomes in Embedded Systems Subject - Ummiati Rahmah; Mahmud Mustapa; Sutarsih Suhaeb; Ratnasari (Ceddi Journal of Education, 2025)
This study aims to evaluate the effectiveness of implementing the Problem-Based Learning (PBL) model in enhancing student learning outcomes in the Embedded Systems course at State Vocational High School (SMKN) 10 Makassar. Traditional lecture-based teaching methods, which still dominate learning activities, are considered less effective in promoting student engagement and deep understanding of the material. To address this limitation, the PBL approach was introduced as an alternative that emphasizes real-world problem-solving and student collaboration. The research employed a quasi-experimental design involving two groups: an experimental group that applied the PBL model and a control group that continued with conventional instructional methods. A validated multiple-choice test, reviewed by subject-matter experts, was used to assess students’ cognitive performance. The findings demonstrate that the application of PBL significantly enhanced learning outcomes. The experimental group achieved a mean post-test score of 19.19, notably higher than the control group’s average score of 12.96. Results from the t-test analysis indicated a statistically significant difference between the two groups (t = 9.821 > t-table = 1.669). Furthermore, the N-Gain score for the experimental group was categorized as moderate (0.53), while the control group’s gain was classified as low (0.15). These results highlight that the PBL model not only strengthens students’ conceptual mastery but also fosters critical thinking abilities and better prepares them to meet challenges in technology-oriented work environments. This study offers valuable insights for enhancing instructional practices within vocational education settings.